Identifying textual silence in scientific research articles. Recontextualizations of the field account in Geology - Dressen, Dacia F. (HERMES - Journal of Language and Communication in Business, 2002)
Long neglected as a primary impetus of study, textual silences abound in such field disciplines as geology, where most field results seem to ‘disappear’ from the published research article. This paper first discusses the nature of textual silence and then proposes a typology of textual silences associated with written scientific discourse. Next, by examining the different disciplinary genres involved in the “recontextualizations” of a fieldwork study in geology, this study seeks to (1) identify textual silence in the various recontextualizations and (2) offer explanations for it.